1988
DOI: 10.1161/01.res.62.6.1191
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ventricular vulnerability to single premature stimuli in open-chest dogs.

Abstract: To determine the mechanism of ventricular vulnerability to electrical stimulation, we simultaneously recorded from 120 transmural electrodes in a 35 X 20 X 5-mm portion of right ventricular infundibulum in seven dogs. Baseline pacing (S1) was performed from outside the mapped region followed by single premature stimulation (S2) of increasing strength at the center of the mapped region. In five of six episodes of ventricular fibrillation and 26 of 30 episodes of repetitive responses, complete reentrant pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 243 publications
(117 citation statements)
references
References 65 publications
4
112
0
1
Order By: Relevance
“…In the computer model (with the two-variable cell model), using the same stimulus protocol that induced reentry in the experimental preparations (12,13), single or paired spiral waves were readily induced ( Fig. 3 A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the computer model (with the two-variable cell model), using the same stimulus protocol that induced reentry in the experimental preparations (12,13), single or paired spiral waves were readily induced ( Fig. 3 A ).…”
Section: Resultsmentioning
confidence: 99%
“…We adapted the right ventricular epicardial sheet preparation described by Davidenko et al (11), consisting of a 1-2 mm thick slice of right ventricular epicardium, ‫ف‬ 25 mm in length and width, pinned down in a chamber and superfused with oxygenated Tyrode's solution at 37 Њ C. Using an S1-S2 stimulation protocol similar to that used to induce ventricular fibrillation in the canine ventricle (12,13), a reentrant arrhythmia consistent with a persistent spiral wave was readily induced, but was very susceptible to spontaneous termination and could not be induced to break up into multiple reentrant wavefronts to simulate a fibrillation-like state. However, after treatment with the ATP-sensitive K ϩ -channel agonist cromakalim (5-10 M) to shorten the action potential duration by 30-50% and reduce wavelength commensurately, a fibrillationlike state could be induced.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most significantly, there was a response, which we have termed a conduction gate, that was selective in its direction, and such gating led to a shifted or reentrant pattern of subsequent excitation. In 1988 Chen et al [2][3][4] initiated a series of studies in ventricular muscle in which macroscopic repolarization gradients were induced by S 1 -S 2 stimuli at different locations. In the presence of macroscopic repolarization gradients, they found that the earliest site of excitation following early premature stimuli occurred consistently at a location between the S 1 and S 2 sites.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is widely known that early premature stimuli initiate reentrant conduction disturbances in the presence of macroscopic gradients of repolarization. [2][3][4][5][6][7] In experimental analyses of these conduction disturbances, the repolarization gradients have been produced primarily by delivering a premature stimulus (S 2 ) at a location distal to the regular stimulus (S 1 ).2-4 Also, 1-D cable models of the associated sodium current events have used this two-stimulus arrangement to create repolarization gradients. 8 Here, all stimuli were given at a single site, so there was no macroscopic repolarization gradient induced by pacing first at one location and then at a second.…”
Section: Introductionmentioning
confidence: 99%